Optimization Studies on the Extraction of Flavone Di-C-glycosides from Premna fulva Craib by Deep Eutectic Solvents. (25th May 2020) - Chen, Yueyuan; Dang, Jiaoyang; Yan, Xiaojie; Lu, Fenglai; Li, Dianpeng
Abstract : Deep eutectic solvents (DESs) are emerging as new extraction solvents for the extraction of bioactive compounds from natural plants. In this work, a total of thirteen choline chloride-based DESs were synthesized and evaluated for the simultaneous extraction of five bioactive flavone di-C-glycosides from Premna fulva Craib. DES-F, which was composed of choline chloride and 1, 3-propanediol, showed the best extraction efficiency for the flavone di-C-glycosides, exceeding that of the conventional industrial solvent (40% ethanol). Subsequently, the extraction parameters for ultrasonic-assisted extraction (liquid-solid ratio, water content (%) in the selected DES, and extraction time) were optimized using response surface methodology. Furthermore, the microstructural alterations in the samples after extraction were evaluated using scanning electron microscopy. In addition, we further verified the recovery of flavone di-C-glycosides from the DESs using macroporous resins and evaluated the reusability of the DESs as solvents. The results indicated that DES-F was an efficient and sustainable solvent for the extraction of bioactive flavone di-C-glycosides from Premna fulva Craib. Therefore, this novel strategy may represent a sustainable approach for the extraction of bioactive products and could make phytochemistry more attractive and environmentally friendly.